The relationship between family well being and aggressiveness among the seventh grade students of junior high school - Lely Ika Mariyati; Widyastuti Widyastuti; Yulvamah Firdausi (Program Studi bimbingan Konseling PPs UNM Makassar, 2021)
This research is aimed to determine the relationship between family well being and the students’ aggressiveness. The proposed hypothesis is that there is a negative relationship between family well being and aggressiveness of junior high school students. Quantitative research method with correlational research was used to conduct this study. The sample of this study was 172 students recruited from 338 students in the population by implementing simple random sampling technique. Likert scale model was used as data collection technique to measure the family well being and aggressiveness. Pearson’s Product Moment correlation technique with the help of SPSS 16.0 for Windows was performed to analyze the data. The results showed that there was -0.225 correlation coefficient with the significance value of 0.001 <0.05, meaning that there is a negative relationship between family well being and aggressiveness among the seventh grade students of a private junior high school in Buduran sub-district. It means that the higher the family well being is, the lower the aggressiveness is and vice versa. Family well being contributes 4.5% to the aggressiveness variable.